Foregut duplication presenting as lingual mass - Bijaylaxmi Behera; Ashish Jain; Siddarth Ramji; Satish Agarwal (Elsevier, 2017)
Congenital cystic masses of the tongue even though detected prenatally are diagnostic challenge even at birth. Very rarely an intestinal duplication cyst may present in the oral cavity leading to difficulty in feeding, swallowing and breathing. These are often diagnosed by histopathologically demonstrating the presence of either gastrointestinal or respiratory epithelium or sometimes both. We present a female newborn with a swelling of the tongue in the oral cavity from birth, interfering with feeding and inability to close the mouth. The swelling was excised by total transoral resection and reconstruction of the tongue was done and confirmed as foregut duplication cyst on histopathological examination. The tongue swelling gradually subsided and the neonate was discharged.